Study of Symptomatic vs. Silent Brain Infarctions on MRI in Elderly Subjects - Raghavan, Sheelakumari; Graff-Radford, Jonathan; Scharf, Eugene; Przybelski, Scott A.; Lesnick, Timothy G.; Gregg, Brian; Schwarz, Christopher G.; Gunter, Jeffrey L.; Zuk, Samantha M.; Rabinstein, Alejandro; Mielke, Michelle M.; Petersen, Ronald C.; et al. (Frontiers in Neurology, 2021)
Brain infarctions are closely associated with future risk of stroke and dementia. Our goal was to report i) frequency and characteristics that differentiate symptomatic versus silent brain infarctions (SBI) on MRI and ii) frequency and location by vascular distribution (location of stroke by major vascular territories) in a population based sample. From Mayo Clinic Study of Aging, 347 participants (≥50 years) with infarcts detected on their first MRI were included. Infarct information was identified visually on a FLAIR MRI image and a vascular territory atlas was registered to the FLAIR image data in order to identify the arterial territory of infarction. We identified the subset with a clinical history of stroke based on medical chart review and used a logistic regression to evaluate the risk factors associated with greater probability of a symptomatic stroke versus SBI. We found that 14% of all individuals with infarctions had a history of symptomatic stroke (Silent: n=300, symptomatic: n=47). Factors associated with a symptomatic versus SBI were size which had an odds ratio of 3.07 (p<0.001), greater frequency of hypertension (odds ratio of 4.12, p=0.025) and alcohol history (odds ratio of 4.58, p=0.012). The frequency of infarcts was greater in right hemisphere compared to the left for SBI. This was primarily driven by middle cerebral artery (MCA) infarcts (right=60%, left=40%, p=0.005). While left hemisphere strokes are more common for symptomatic carotid disease and in clinical trials, right hemispheric infarcts may be more frequent in the SBI group.